Data Africa - HarvestChoice; Data Wheel (International Food Policy Research Institute, 2017)
Data Africa is an open data visualization platform designed to provide information on key themes for research and development, such as agriculture, climate, poverty and child health across 13 countries in Africa South of the Sahara at the sub-national level. Users of the tool can explore and visualize location-specific data from various sources including HarvestChoice’s data products such as CELL5M ( http://dx.doi.org/10.7910/DVN/G4TBLF ) and Spatial Production Allocation Model ( http://dx.doi.org/10.7910/DVN/DHXBJX ), as well as the reanalysis of secondary datasets from University of East Anglia Climatic Research Unit ( http://www.cru.uea.ac.uk ), World Bank PovcalNet ( http://iresearch.worldbank.org/PovcalNet ), and USAID DHS Program ( http://dhsprogram.com ). The main goal of the online tool is to present the themes to a wide, even non-technical audience through easily accessible visual narratives. Data Africa is a HarvestChoice website. Development of Data Africa was undertaken as part of the HarvestChoice project and the CGIAR Research Program on Policies, Institutions, and Markets (PIM), led by the International Food Policy Research Institute (IFPRI), in collaboration with Datawheel and Barefoot Education for Afrika Trust (BEAT). Funding support for this platform was provided by the Bill and Melinda Gates Foundation and USAID Bureau for Food Security. The visualizations in Data Africa are powered by D3plus ( http://d3plus.org ), an open-source visualization engine that was created by Datawheel. Contents in this website have not gone through IFPRI’s standard peer-review procedure. The opinions expressed here belong to the authors, and do not necessarily reflect those of PIM, IFPRI, or CGIAR.